Inclusive education for a democratic society - Casanova, Mª Antonia (Avances en Supervisión Educativa, 2011)
The only educational model that meets the requirements of a democratic society is inclusive. Merely because of the principles and philosophy that characterize democracy, respect for differences, appreciation of it as a common wealth, participation of the entire population in government decisions, consideration of the valuable contributions of all citizens, a practice equal rights and opportunities ... in short, a society that, as with all must train all so they can properly exercise their rights in all spheres of life and who can bring their personal values ??of critical and creativity to help them advance in the way of social improvement permanent.